Implementasi Lesson Study Menerapkan Model STAD Untuk Meningkatkan Interaksi, Eksplorasi, dan Motivasi Siswa Pada Bahasan Dispersi di Kelas XII IPA SMA Negeri I Pontianak - Khaeriyah, Siti; ., Shofiyati; Maliku,, Astin; Yetty, Dede (Jurnal Pendidikan Matematika dan IPA, 2011)
The aim of this study is to find out the implementation of lesson study implementing STAD model to improve interaction, exploration and motivation of student in the dispersion topic at the XII IPA class of SMA Negeri 1 Pontianak. This research is a descriptive study that uses LKS instrumen to control the concept, assessment questionnaire response of students towards learning and observation sheet. Students who became the subject of this research is XII IPA 1 students of theschool year 2011-2012. Based on discussion and reflection, we can conclude that 1) The implementation of lesson study can improve the students interaction one another, 2) The implementation of lesson study can improve the exploration by teachers to the students, 3) Lesson study activity on the subject of disperion can enhance students movation. Key words: lesson study, dispersion, interaction, exploration, motivation